REFORMULASI PENETRATION STRESS TEST SEBAGAI PERLINDUNGAN HUKUM DATA PRIBADI KONSUMEN DI ERA BISNIS DIGITAL - Parvez, Abel; Superani, Andi Vallian; Anta Maulana, Muhammad Hasyim (Justitia et Pax, 2023)
This research focus on consumer personal data protection as a part of invention from privacy right in digital era. The high number of consumer personal data utilization by electronic system operator not accompanied with decent penetration stress test (PST) regulation. The purpose of this research is to give solution to clear personal data protection problem through PST testing method. The method that used by this research is normative research through statutory approach and conceptual approach. The result from this research concludes that there are still many problematic PST regulation. The problem can be seen from personal data protection that shattered in 30 statutory from different sector with no one arrange PST comprehensively. This dispute culminates to emergence dissimilarity definition, overlapping authority between receiver of System Management Security Information certification annual report, and PST operator polemic. As the result, it causes rampant of personal data breach that inflict consumer by matter, along with specific data exploitation that lead to sluggish business and economic country. Therefore, PST testing reformulation is needed as prevention step to protect consumer personal data in digital business era.